Psychological Distress, Hope and Quality of Life Among Cardiac Patients: A Correlational Study - Malaika Tariq,; Muhammad Numan Munir,; Rimsha Afzal,; Usama,; Farzana Afzal,; Komal Younas, (Dialogue Social Science Review (DSSR), 2024)
The aim of this research was to investigate the connection between psychological distress, hope, and quality of life in individuals with heart conditions. A correlational research approach was employed, and 200 cardiac patients (100 men and 100 women) were chosen using purposive sampling from different public hospitals in Faisalabad. Various tools including a Demographic Form, Quality of Life Scale, Hope Index, and Psychological Distress Scale were utilized to assess the variables. The Statistical Package for Social Sciences (SPSS) was used to analyze the data. The results of correlation analysis revealed a strong negative relationship between psychological distress and hope, as well as between psychological distress and quality of life. Conversely, a strong positive correlation was found between hope and quality of life. Additionally, the linear regression analysis indicated that psychological distress significantly predicted hope and life quality in cardiac patients. Furthermore, the t-test analysis demonstrated that female cardiac patients exhibited significantly higher levels of psychological distress compared to male patients, while male patients scored significantly higher in hope and quality of life than female patients. These findings could be utilized to advocate for policies that ensure access to mental health support in cardiac care settings and may lead to further research into effective strategies for enhancing hope and reducing psychological distress to improve the life quality for diverse patient populations.